The roles of environmental pollutants in the pathogenesis and prevalence of diabetes: a review - T Yahaya; I Obaroh; E.O. Oladele (Journal of Applied Sciences and Environmental Management, 2017)
Diabetes is on the rise worldwide with a growing suspicion of association between environmental pollutants and diabetes. This paper reviewed the roles of environmental pollutants in the pathogenesis and increasing incidence of diabetes. Relevant information was retrieved from reliable sources in the internet using Google search engine. The review found that studies have established environmental pollutants aid in the pathogenesis of diabetes by causing blood vessel rupture and insulin resistance. Toxic chemicals in pollutants may destroy or cause mutation in pancreatic β-cells, disrupting its insulin production. People are therefore advised to live far away from polluted or industrial environment.